Insufficient recovery of fractional flow reserve even after optimal implantation of drug-eluting stents: 3-year outcomes from the FUJI study. Issue 5 (May 2021) - Hokama, Yohei; Tanaka, Nobuhiro; Takashima, Hiroaki; Kadota, Kazushige; Fujita, Hiroshi; Tan, Michinao; Yamada, Ryotaro; Naruse, Hiroyuki; Kawamura, Akio; Suzuki, Nobuaki; Takeuchi, Tsuyoshi; Tazaki, Junichi; et al.
Highlights: We investigated the clinical implication of post-stent fractional flow reserve (FFR). Inadequate FFR group was significantly associated with high major adverse cardiovascular events (MACE). Inadequate FFR group affected high incidence of non-target lesion revascularization in MACE. Post-stent FFR may be a surrogate marker for atherosclerosis in whole of the coronary artery. Abstract: Background: Adequate improvement in fractional flow reserve (FFR) is not necessarily achieved in some cases of drug-eluting stent (DES) implantation, even when imaging confirms successful placement. We hypothesized that post-stent FFR may be associated with advanced diffuse atherosclerotic condition. We explored the relationships between FFR values after DES implantation (post-stent FFR). Methods: A total of 218 patients were included in this prospective, multicenter study and were divided into two groups: adequate FFR group (post-stent FFR >0.80, n =176) and inadequate FFR group (post-stent FFR ≤0.80, n =42). The primary endpoint was a major adverse cardiovascular event (MACE) including cardiac death, non-fatal myocardial infarction (MI), unplanned coronary revascularization, and hospitalization for heart failure. The secondary endpoints were event rate of all-cause death, non-fatal MI, unplanned coronary revascularization, non-fatal stroke, and hospitalization for heart failure. Results: During follow-up of 31.4±8.7 months, 34 patients (16%) had cardiovascular events. Inadequate FFR group was significantly associated with higher risk of MACE (hazard ratio: 3.86; 95% confidence interval: 1.17–12.76, p =0.026; log-rank p =0.027). In particular, the incidence of unplanned coronary revascularization on non-target lesions was significantly higher in the inadequate FFR group (log-rank p =0.031). Conclusions: Post-stent FFR ≤0.80 was associated with a high incidence of non-target lesion revascularization and could be a surrogate marker for advanced atherosclerotic condition in the vessels of the entire coronary artery.